COMPARATIVE STUDY OF METHODS FOR SOLVING THIRD-ORDER ORDINARY AND PARTIAL DIFFERENTIAL EQUATIONS IN IRREGULAR GEOMETRIES DOMAINS (International Journal of Food and Nutritional Sciences, 2022)
In the mathematical toolbox for differential equations, the Adomian decomposition and Laplace transform techniques each have defined functions. Iteratively breaking down complicated differential equations into smaller, easier-to-manage components is a hallmark of the Adomian decomposition method, which is particularly helpful for nonlinear issues. By transforming linear ODEs and PDEs with constant coefficients into algebraic equations, the Laplace transform approach, on the other hand, makes it easier to solve them by algebraic manipulation.